The Influence of Virtual Education on the Knowledge Level of Adolescents Regarding the Dangers of Dental Technician - Sari Aldilawati; Muhammad Jayadi Abdi; Anggita Maulidya Putri (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Education is the process of learning from unknown to know or to understand it. Dental and oral health education aims to help increase public awareness by providing knowledge. A dentist is anyone who has the skills to make and install removable dentures. The work that a dentist should do cannot be compared to that of a dental technician. Material and Method: Quasi-experimental research design with a one group pretest-posttest design by testing the same questionnaire twice, namely before and after education. Results and Discussions: Based on the results of the paired sample t-test, a p-value of 0.00 was obtained, which is lower than the predetermined significance level value of 0.05, so that Ha is accepted, which means that there is any influence of virtual education on the level of knowledge in teenagers about the dangers of dentist victim. Conclusion: There is an influence of virtual education about the dangers of dentist victims on the level of knowledge of teenagers at Garudaya Bontonompo Vocational School.